Does the belt and road initiative stimulate Chinese exports? The role of state-owned enterprises - Holger Görg; Haiou Mao (Kiel Institute for the World Economy (IfW), 2020)
This paper evaluates firms' exporting responses to BRI and considers their heterogeneity in ownership types, product types, regional origin and trade mode. This is done by analyzing firm-product-destination level customs data from 2011 to 2015 in a gravity model framework. Our empirical results show that aggregate export behavior did not change significantly after BRI. However, ownership matters when evaluating firms' reactions. SOEs increase their total exporting and average export value (the intensive margin) to BRI countries, while private domestic firms show no reaction to BRI at any margin. Further, our results on regional heterogeneity suggests that "open through the west", i.e., boosting the development of western regions in China, did not appear to work in the short term. Our findings show clearly the implications of BRI's impact from a firm level perspective.
Keywords: F10; O24; 330; Belt and Road Initiative; firm's export; extensive margin; intensive margin; state-owned firms